Agreement between clinical and portable EMG/ECG diagnosis of sleep bruxism. (7th June 2015) - Castroflorio, T.; Bargellini, A.; Rossini, G.; Cugliari, G.; Deregibus, A.; Manfredini, D.
Summary: The aim of this study was to compare clinical sleep bruxism (SB) diagnosis with an instrumental diagnosis obtained with a device providing electromyography/electrocardiography (EMG/ECG) recordings. Forty‐five ( N = 45) subjects (19 males and 26 females, mean age 28 ± 11 years) were selected among patients referring to the Gnathology Unit of the Dental School of the University of Torino. An expert clinician assessed the presence of SB based on the presence of one or more signs/symptoms (i.e. transient jaw muscle pain in the morning, muscle fatigue at awakening, presence of tooth wear, masseter hypertrophy). Furthermore, all participants underwent an instrumental recording at home with a portable device (Bruxoff ® ; OT Bioelettronica, Torino, Italy) allowing a simultaneous recording of EMG signals from both the masseter muscles as well as heart frequency. Statistical procedures were performed with the software Statistical Package for the Social Science v. 20.0 (SPSS 20.0 ® ; IBM, Milan, Italy). Based on the EMG/ECG analysis, 26 subjects (11 males, 15 females, mean age 28 ± 10 years) were diagnosed as sleep bruxers, whilst 19 subjects (7 males, 12 females, mean age 30 ± 10 years) were diagnosed as non‐bruxers. The correlation between the clinical and EMG/ECG SB diagnoses was low ( ϕ value = 0·250), with a 62·2% agreement (28/45 subjects) between the two approaches (kappa = 0·248). Assuming instrumental EMG/ECG diagnosis as the standard of reference for definite SB diagnosis in this investigation, the false‐positive and false‐negative rates were unacceptable for all clinical signs/symptoms. In conclusion, findings from clinical assessment are not related with SB diagnosis performed with a portable EMG/ECG recorder.